Bagaimana Guru Mengembangkan Profesionalisme Mereka melalui Motivasi Intrinsik dan Ekstrinsik? Studi Literatur - Laila Latifah Dinillah; Suyatno; Dian Hidayati (Universitas Sarjanawiyata Tamansiswa, 2026)
In the digital era marked by rapid technological and educational advancements, the development of teacher professionalism is a crucial aspect in realizing the educational goals of Indonesia. This literature study aims to investigate the influence of intrinsic and extrinsic motivation on the development of teacher professionalism. Using a systematic literature review approach, 33 relevant articles from credible databases (Google Scholar, Springer Link, and Science Direct) were analyzed focusing on motivation, intrinsic motivation, extrinsic motivation, teacher professionalism, and its development. The findings indicate that both intrinsic motivation, driven by internal desires such as interest, responsibility, and self-improvement, and extrinsic motivation, arising from external factors like rewards, recognition, and organizational support, play significant and complementary roles in fostering teacher professionalism. Intrinsic motivation encourages active engagement, creativity, and sustained commitment, while extrinsic motivation provides structure and reinforcement through training, incentives, and supportive leadership. The synergy between these motivations, supported by a conducive educational environment that fulfills teachers’ needs for autonomy, competence, and social relatedness, optimizes professional growth and positively impacts teaching quality and student outcomes. Therefore, strategies to enhance teacher professionalism should integrate approaches that nurture intrinsic motivation alongside appropriate extrinsic supports.